Fenomena Gangguan Kepribadian Antisosial dan Narsistik Terhadap Perilaku Narapidana - Adinda Nur Oktafia Rosadi; Siti Faedattusyahadah; Sandora Afita; Annisa Darmaji Putri; Dhimas Petrik Simanjuntak; Tugimin Supriyadi (Observasi : Jurnal Publikasi Ilmu Psikologi, 2025)
The types of personality disorders often associated with criminal behavior in prisoners are antisocial personality disorder and narcissistic personality disorder. Antisocial Personality Disorder is a personality disorder characterized by a pattern of indifference and violation of the rights of others, which usually begins in childhood or early adolescence and continues into adulthood. Meanwhile, Narcissistic Personality Disorder (NPD) is a psychological disorder characterized by patterns of excessive superiority, fantasies of power or extraordinary importance, and the need for admiration or special treatment. The method in this study uses a descriptive method with literature study data collection techniques involving the study of theories and references related to values, culture, and norms that apply in the social context under study. Literature study is an important step in research because research always depends on scientific literature. Literature study was conducted for data analysis in this research. Research data was obtained from relevant sources, such as books, journals, articles, and previous research, through literature study.